The Arctic Terrestrial Biodiversity Monitoring Plan. CAFF Monitoring Series Report No. 7. (FINAL DRAFT FOR CAFF BOARD REVIEW). - Christensen, T.; Payne, J.; Doyle, M.; Ibarguchi, G.; Taylor, J.; Schmidt, N.M.; Gill, M.; Svoboda, M.; Aronsson, M.; Behe, C.; Buddle, C.; Cuyler, C.; et al. (CAFF International Secretariat, 2013)
Final draft for CAFF board review of the Arctic Terrestrial Biodiversity Monitoring Plan / CAFF Monitoring Series Report No. 7. Presented at the Arctic Council's Senior Arctic Officials meeting in Whitehorse, Canada, October 22-23 2013. NOTE: This document is not the finally approved version of the report, and should therefore not be quoted as such.